2016
DOI: 10.1589/jpts.28.2376
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 12-week complex training on the body composition and cardiorespiratory system of female college students

Abstract: [Purpose] The aim of this study was to examine the effects of a complex exercise program on the body composition and cardiorespiratory system of female college students. [Subjects and Methods] This study included 20 female college students who had not participated in any particular sports in the last 3 months. The complex exercise program consisted of two parts, aerobic exercise and weight training. First, aerobic exercise was implemented (30 min 5 times a week for 12 weeks) according to the participants’ exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…The current study used six, 30-min interviews over six months, which is a much less intensive intervention comparatively, and found a difference of 2.43 % in body fat between the two groups at the end of the study, which is similar to the difference of 2.5 % reported by Mustedanagic et al. [ 44 ], though less than the 5.5 % loss from pre to post among the intervention conducted by Kim & Han [ 45 ]. Most of the interventions addressing weight status among college students also appear to be short-term interventions (10–12 weeks) versus the six-month intervention in this study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The current study used six, 30-min interviews over six months, which is a much less intensive intervention comparatively, and found a difference of 2.43 % in body fat between the two groups at the end of the study, which is similar to the difference of 2.5 % reported by Mustedanagic et al. [ 44 ], though less than the 5.5 % loss from pre to post among the intervention conducted by Kim & Han [ 45 ]. Most of the interventions addressing weight status among college students also appear to be short-term interventions (10–12 weeks) versus the six-month intervention in this study.…”
Section: Discussionsupporting
confidence: 80%
“…Mustedanagic’ and team [ 44 ] utilized skinfolds to measure body composition and found that after 36 aerobic and resistance training sessions over 12 weeks lasting 60 min, there was a significant decrease in body fat percentage and a significant increase in lean mass percentage. Another study utilized biological impendence to measure body fat percentage and skeletal muscle after a very intensive intervention of 60 aerobic and 60 resistance training sessions over 12 weeks and found significant decreases in body fat percentage and a significant increase in skeletal muscle pre to post [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CT usually involves the combination of two biomechanically similar exercises with the high-load resistance exercise performed first (e.g., squat at 90% of one-repetition maximum), followed by the low-load plyometrics training (e.g., squat jumps) ( Fleck and Kontor, 1986 ; Thapa et al, 2020 ). Studies have shown that CT can improve sports performance ( Kim and Han, 2016 ; Abade et al, 2020 ; Gee et al, 2021 ). More recently, studies have emerged showing that CT can help the development and maintenance of muscle strength ( Wallenta et al, 2016 ; Jones et al, 2019 ; Thapa et al, 2020 ) and power ( Jones et al, 2019 ; Pagaduan and Pojskic, 2020 ), and sprint ability ( Freitas et al, 2017 ; Abade et al, 2020 ; Thapa et al, 2020 ), with shorter and more flexible training schedule and lower risk of injury ( Chatzinikolaou et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also shown that volleyball training can improve cardiovascular health, muscular strength, and endurance [24,25]. In addition, volleyball has been shown to have a positive impact on bone health and can reduce the risk of osteoporosis [26].…”
Section: Discussionmentioning
confidence: 99%